N-acetycysteine: A potential therapeutic agent in COVID-19 infection. (November 2020) - Jaiswal, N; Bhatnagar, M; Shah, H
Abstract: COVID-19 is an overwhelming pandemic which has shattered the whole world. Lung injury being the main clinical manifestation, it is likely to cause COPD (chronic obstructive pulmonary disease) and ARDS (acute respiratory distress syndrome). The possible cause behind this might be redox imbalance due to viral infection. Elevation in Glutathione (GSH) levels by administration of its promolecule might be effective. N-acetylcysteine is one such drug with potency to scavenge Reactive Oxygen Species, least side effects, and an effective precursor of glutathione. Consequently we hypothesize that N-acetylcysteine along with the conventional treatment may be treated as a potential therapeutic solution in cases of COVID-19 patients.